Healthcare-related infection and the challenges faced by nurses with regard to control measures: An integrative review (Research, Society and Development, 2024)
Objective: to identify in the literature the difficulties encountered by nurses and investigate coping strategies regarding control measures for Healthcare-Associated Infections. Method: integrative literature review, through articles available in the databases - Public MEDLINE, Latin American and Caribbean Literature in Health Sciences, Nursing Database, Scopus, Scientific Electronic Library Online, Cumulative Index to Nursing and Allied Health Literature and Web of Science written databases in Portuguese, Spanish and English, which were in full, published between the period 2015 and 2020. Publications of the review type, conference summaries, proceedings, editorials, letters and repeated news, review studies, as well as research not available in full and free of charge or that did not answer the research question outlined. Result: 25 articles were found from various parts of the world. The data was organized in a table that allows observing the study code, country of origin, authors, year of publication and categorized results. Conclusion: the reality regarding infection control is complex due to the lack of adherence, effective involvement in the safety culture and infection prevention. Capacity building, training, attendance, awareness raising and the practice of diverse educational interventions can have a positive impact on infection control measures.